Al-Qarinah: antara kekuatan dan keperluan dalam mensabitkan kesalahan jenayah (zina) - Lukman Abdul Mutalib,; Wan Abdul Fattah Wan Ismail, (Universiti Kebangsaan Malaysia, 2012)
Justice is the ultimate objective of any judiciary system. The absolute justice is only belongs to Islamic judiciary system. However it is highly dependant on the quality of the implementation methodology that man could produce. In the Islamic judiciary system, especially to convict a zina, there are various methods in establishing evidence. Some of the methods are unanimously accepted while some others are not unanimously accepted. Al-qarinah is among those which are not unanimously accepted by the Islamic jurists. The Islamic law is actually dynamic. The dynamism lies on its flexibility, which is the main characteristic of the law itself. It is because the fiqh law is not isolated from reality, but derived from the analysis on the contemporary environments. The development in science and technology has changed the human civilisation and perception towards life. The development of knowledge in producing evidence scientifically such as DNA test, fingerprint etc. coupled with the more complex criminal behaviour, demand us to take a detailed and in-depth study to determine the status of al-qarinah in the contemporary Islamic judiciary system in order to make sure an Islamic law is relevant and effort to give a justice and positive perception among nation toward Islam.